(untitled) - Reid, Michelle; Lieber, Rochelle (New York, 2012)
Includes bibliographical references and index; The Purpose of Reports -- Gathering Your Information -- Structuring Your Report -- Business Plans, Project Proposals and Dissertations -- Presenting Your Findings -- Writing Concisely -- Report Writing at Work
Keywords: Report writing -- Research; Viết báo cáo -- Nghiên cứu; English language -- Rhetoric; Ngôn ngữ Anh -- Hùng biện